Pengantar editor-in-chief Mediapsi volume 7 nomor 1 tahun 2021 - Mashuri, Ali (Mediapsi, 2021)
Mediapsi published 7 empirical articles for its new edition, i.e., volume 7 issue 1, 2021, which cover multifarious topics and research methods. The first article is qualitative research aimed at investigating the self-adjustment of a postgraduate who works while studying. The second article focuses on undergraduate students’ academic burnout and explained quantitatively this phenomenon based on various forms of social support. The third article is meta-analysis research to synthesize the extent to which mindfulness-based interventions are effective in increasing resilience at the workplace. The fourth article applied a qualitative method that also touches upon the topic of resilience but within a different context, that is, community resilience amid the COVID-19 pandemic. The fifth article, the same as the third article, is meta-analysis research to examine to what extent music therapy has a significant effect as an intervention in improving sleep quality. The sixth article is an experimental research that tested the effect of virtual reality on the induction of negative emotions. The seventh, last article also examined the phenomenon of social support explained its role in explaining subjective well-being among a sample of ethnic Minang adolescents.Dalam volume 7 nomor 1 tahun 2021 ini, Mediapsi mempublikasikan tujuh artikel empiris dengan topik dan metode penelitian yang bervariasi. Artikel pertama menerapkan metode kualitatif untuk meneliti adaptasi atau penyesuaian-diri mahasiswa yang kuliah sambil bekerja. Artikel kedua mengangkat tema atau topik tentang academic burnout di kalangan mahasiswa yang dijelaskan secara kuantitatif atas dasar berbagai bentuk social support. Artikel ketiga merupakan studi meta-analisis untuk menguji sejauh mana intervensi berbasis mindfulness efektif untuk meningkatkan resiliensi di tempat kerja. Artikel keempat menerapkan metode kualitatif yang juga membahas topik tentang resiliensi tetapi dalam konteks yang berbeda, yaitu resiliensi komunitas di tengah pandemi COVID-19. Artikel kelima, seperti artikel ketiga, adalah studi meta-analisis yang bertujuan untuk menyimpulkan sejauh mana musik terapi berpengaruh signifikan sebagai intervensi dalam meningkatkan kualitas tidur. Artikel keenam merupakan riset eksperimen yang menguji sejauh mana virtual reality berpengaruh dalam menginduksi emosi-emosi negatif. Artikel ketujuh sekaligus terakhir juga meneliti dukungan sosial atau social support dan menguji perannya terhadap subjective well-being di kalangan remaja etnis Minang.